Evaluation of Post-OP Complications using Risk Assessment Tool; Attitude of Surgeons - Hafiz Muhammad Ali Hasnain, Muhammad Hamza, Muhammad Faisal Javaid, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Current study was designed to assess the attitude of surgeons towards the use of surgical risk assessment tools in Sargodha. Method: This study was of descriptive crossectional nature. It was a survey based study conducted in a 4 tertiary care hospitals of Sargodha. Data of 30 surgeons was collected using a questionnaire. Frequencies and percentages were calculated to interpret results. Results: The usage of online risk calculator was never used by majority of surgeons (83.33%). Risk assessment is always based on prior experience (76.67%). Evaluation of risk assessment based on existing literature is always practiced by 53.33% surgeons. Conclusion: majority of surgeons are not using risk assessment calculator in surgical settings. They are focusing on prior experience based assessment of post-op complications. The briefing time given by surgeon to the patients while communicating their risk assessment is very less which should be maintained by the hospital management.